Life history traits and demographic parameters of Triatoma infestans (Hemiptera: Reduviidae) fed on human blood - Medone, Paula (2015)
Triatoma infestans (Klug, 1834) (Hemiptera: Reduviidae), the main vector of Chagas disease in South America, feeds primarily on humans, but ethical reasons preclude carrying out demographical studies using people. Thus, most laboratory studies of T. infestans are conducted using bird or mammal live hosts that may result in different demographic parameters from those obtained on human blood. Therefore, it is of interest to determine whether the use of an artificial feeder with human blood would be operational to rear triatomines and estimate population growth rates. We estimated life history traits and demographic parameters using an artificial feeder with human blood and compared them with those obtained on live hens. Both groups of T. infestans were kept under constant conditions [28 6 1C, 40 6 5% relative humidity, a photoperiod of 12:12 (L:D) h] and fed weekly. On the basis of age-specific survival and age-specific fecundity, we calculated the intrinsic rate of natural increase (r), the finite rate of population growth (k), the net reproductive rate (Ro), and the mean generation time (Tg). Our results show differences in life history traits between blood sources, resulting in smaller population growth rates on human blood than on live hens. Although demographic growth rate was smaller on human blood than on hens, it still remains positive, so the benefit/cost ratio of this feeding method seems relatively attractive. We discuss possibility of using the artificial feeder with human blood for both ecological and behavioral studies.